The Behavior of KBF4 in Potassium-Cryolite-Based Melts. Issue 4 (1st January 2015) - Kataev, A.; Tkacheva, O.; Redkin, A.; Rudenko, A.; Dedyukhin, A.; Zaikov, Yu.
Abstract : The KBF4 impact on the physical-chemical properties of the KF-AlF3 and KF-NaF(10 wt%)-AlF3 melts with cryolite ratio (CR) 1.3–1.5 was studied at temperatures 700–800°C. The KBF4 additions (up to 15 mol%) to the potassium-cryolite-based electrolytes increase the liquidus temperature, however, the KBF4 presence in the cryolite-alumina melt improves the Al2 O3 solubility and enlarges the range of homogeneity in the (cryolite-KBF4 )-Al2 O3 system. The KBF4 additions (within a concentration range of 0–10 mol%) do not noticeably impact the electrical conductivity of the KF-AlF3 -KBF4 melt (CR = 1.3). The mass loss of the KF-AlF3 -KBF4 samples with low CR determined by thermogravimetry analysis over two hours is not higher than 3% at temperature 800°C.